Paramagnetic salt and agarose recipes for phantoms with desired T1 and T2 values for low‐field MRI - Jordanova, Kalina V. (2024)
Tissue-mimicking reference phantoms are indispensable for the development andoptimization of magnetic resonance (MR) measurement sequences. Phantoms havegreatest utility when they mimic the MR signals arising from tissue physiology;however, many of the properties underlying these signals, including tissue relaxationcharacteristics, can vary as a function of magnetic field strength. There hasbeen renewed interest in magnetic resonance imaging (MRI) at field strengths lessthan 1 T, and phantoms developed for higher field strengths may not be physiologicallyrelevant at these lower fields. This work focuses on developing materials with specific relaxation properties for lower magnetic field strengths. Specifically, we developed recipes that can be used to create synthetic samples for target nuclear magnetic resonance relaxation values for fields between 0.0065 and 0.55 T. T1 and T2 mixing models for agarose-based gels doped with a paramagnetic salt (one of CuSO4, GdCl3, MnCl2, or NiCl2) were created using relaxation measurements of synthetic gel samples at 0.0065, 0.064, and 0.55 T. Measurements were evaluated for variability with respect to measurement repeatability and changing synthesis protocolor laboratory temperature. The mixing models were used to identify formulations ofagarose and salt composition to approximately mimic the relaxation times of five neurologicaltissues (blood, cerebrospinal fluid, fat, gray matter, and white matter) at0.0065, 0.0475, 0.05, 0.064, and 0.55 T. These mimic sample formulations were measuredat each field strength. Of these samples, the GdCl3 and NiCl2 measurementswere closest to the target tissue relaxation times. The GdCl3 or NiCl2 mixing modelrecipes are recommended for creating target relaxation samples below 0.55 T. Thiswork can help development of MRI methods and applications for low-field systemsand applications.